Digitally Assisted, Fully Integrated, Wideband Transmitters for High-Speed Millimeter-Wave Wireless Communication Links - del Rio, David; Rezola, Ainhoa; Sevillano, Juan F.; Velez, Igone; Berenguer, Roc.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents design methods and considerations for digitally-assisted wideband millimeter-wave transmitters. It addresses comprehensively both RF design and digital implementation simultaneously, in order to design energy- and cost-efficient high-performance transmitters for mm-wave high-speed communications. It covers the complete design flow, from link budget assessment to the transistor-level design of different RF front-end blocks, such as mixers and power amplifiers, presenting different alternatives and discussing the existing trade-offs. The authors also analyze the effect of the imperfections of these blocks in the overall performance, while describing techniques to correct and compensate for them digitally. Well-known techniques are revisited, and some new ones are described, giving examples of their applications and proving them in real integrated circuits. Discusses the design of mm-wave transceivers from both the analog and digital design perspectives; Analyzes different well-known architectures and revisits some key aspects in order to make them suitable for mmW circuits; Covers design considerations at the system, block/circuit and transistor levels of abstraction; Enables readers to build high-performance, energy and cost-efficient mm-wave radios; Addresses circuit reliability and sensibility to environmental variations, in order to implement robust and auto-adjustable systems; Analyzes quantitatively the effect of different imperfections on the performance of the whole system, and proposes different methods to compensate for them and mitigate their effects; Applies design techniques described in real examples, demonstrating the transmission of multi-Gbps signals.
Introduction -- System level analysis of millimeter-wave wireless links -- Effect of Front-End Imperfections on Wideband Millimeter-Wave Signals -- Digital Compensation and Mitigation of I/Q gain and Phase Imbalance -- Design Methodology for BiCMOS mmW Integrated Circuits -- Upconverters -- Power Amplifiers -- Power Detectors -- A Fully Integrated and Digitally Assisted BiCMOS Transmitter for a 10-Gbps Wireless Link in the E-band.
Keywords: Electronic circuits; Signal processing; Telecommunication; Electronic Circuits and Systems; Signal, Speech and Image Processing; Communications Engineering, Networks